Behavioral cognitive therapy to reduce cyberbullying behavior in adolescents during the Covid-19 Pandemic - Nuzulawati, Mety Tri Nur; Astuti, Kamsih (International Journal for Educational and Vocational Studies, 2022)
The purpose of this study was to determine the difference in the level of cyber bullying between the group that was given cognitive behavioral therapy and the group that was not given cognitive behavioral therapy. In addition, measuring the level before and after being given cognitive behavioral therapy in adolescents. The method used in this research is an experimental approach study. The results of the analysis using the Mann Whitney-U test measure cyber bullying in the experimental group that was given cognitive behavioral therapy and the control group that was not given therapy with a pre-test Z score Z = -1.781 with Asymp. Signature (2-tailed) 0.075 and post-test Z score -2.619 with 0.009, which means that there is a difference in the level of cyber bullying in adolescents between the experimental group and the control group. The results of the Wilcoxon Rank test to measure the pretest-posttest obtained a value of Z = -2.527 and p = 0.012 (p>0.05), while for the posttest-follow-up Z score of -2.217 with p = 0.27 means that there are differences in cyber levels. bullying before and after, and after the follow-up was given cognitive behavioral therapy in the experimental group which means a decrease in the level of cyber bullying in the experimental group.